Kasus ‘Baiq Nuril’ Sebagai Refleksi Pembelajaran Guna Meningkatkan Mutu Etika Profesi Kependidikan - Permana, I Dewa Gede Darma (LPM IHDN Denpasar, 2021)
The 'Baiq Nuril' case is a case involving a former honorary teacher at SMAN 7 Mataram, West Nusa Tenggara (NTB), named Baiq Nuril Maknun with his superior, Mr. Muslim, who is the principal of SMAN 7 Mataram. In this regard, this study is interested in examining the case to find out the reflection of its learning in order to improve the quality of educational professional ethics. In this study, several problems were also formulated, namely related to the complete chronology of the 'Baiq Nuril' case, regarding the ethics of the educational profession related to the 'Baiq Nuril' case, along with the reflection of learning from the case as an increase in the quality of educational professional ethics. This study uses a case study research type, with data collection methods using library research techniques and using data analysis from Miles and Huberman. The results of this study indicate that there are several educational professional ethics that were violated in the 'Baiq Nuril' case, especially those concerning the personal competence of education personnel. Through this research, it is hoped that it can provide a reflection of learning so that similar cases do not happen again in the future, and are useful in improving the ethics of the educational profession.